Effect of Manual Fruit Thinning and CPPU on the Fruit Yield and Changes in Physico-chemical Composit ion at Harvest and af ter Storage of Allison Kiwifruit - Babita; Rana, Vishal S. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out in the Kiwifruit Block of Department of Fruit Science, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni-Solan (H.P.) during the year 2011-12 on 27-year-old Kiwifruit cv. Allison comprising of manual fruit thinning alone and in combination with 5 ppm CPPU. This experiment included 8 treatments viz., control, 5 ppm CPPU, thinning up-to 4 fruits shoot-1, thinning up-to 4 fruits shoot-1+5 ppm CPPU, thinning up-to 6 fruits shoot-1, thinning up-to 6 fruits shoot-1+5 ppm CPPU, thinning up-to 8 fruits shoot-1 andthinning up-to 8 fruits shoot-1+5 ppm CPPU. The CPPU (urea based cytokinin) was applied as a fruit dip treatment after 10 days of petal fall. The maximum average fruit weight (105.64 g), length (7.48 cm) and diameter (4.96 cm) were found with manual thinning of 4 fruits shoot-1 along with dip treatment in 5 ppm CPPU. The highest (16.54 g) % loss in weight was recorded with thinning up-to 6 fruits shoot-1+5 ppm CPPU). The highest TSS contents (7.78, 15.47%), minimum acidity (1.35, 0.74%), highest total sugars (4.19, 9.88%), maximum TSS acid ratio (5.78, 21.04), highest ascorbic acid (90.13, 64.53 mg 100 g-1) content at harvest and after storage, respectively, were also found with the treatment T4. However, the highest (87.26 k vine-1) fruit yield was recorded in vines, retained with 8 fruits shoot-1 along with the application of 5 ppm CPPU.